MEKANISME IMPLEMENTASI SIDANG PENYELESAIAN SENGKETA INFORMASI PUBLIK (AJUDIKASI NON LITIGASI) DI KOMISI INFORMASI PROVINSI KALIMANTAN SELATAN - Tamliha Harun (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The title of this research is: "Mechanism of Implementation of Public Information Dispute Settlement Session (Non-Litigation Adjudication) at Information Commission of South Kalimantan Province". This research was conducted with the intention to provide input to the Information Commission of South Kalimantan Province in an effort to improve its performance, especially in the implementation of public information dispute resolution session (non litigation adjudication). And also to inform the public, so all of them know and understand how the mechanism of public information dispute resolution session inInformation Commission. This research is a descriptive research, with its data collection techniques : interview, observation, and documentation, then analyzed qualitatively. The result of the research shows that : The mechanism of implementation of public information dispute resolution in Information Commission of South Kalimantan Province has been implemented in accordance with the provisions regulated by Undang-undang Nomor 14 Tahun 2008 About KIP and PERKI Nomor 1 Tahun 2013 About Public Information Dispute Procedure. In order for the implementation of public information dispute resolution hearing in the Information Commission to work better and professional, it is recommended that the commissioners need to follow the education/ non-litigation adjudication mediation training and secretariat follow the education/ training of registrant, and supported by representative facilities and infrastructure in the implementation of information dispute resolution session.